Preserving African Heritage: Curatorial and Public Perspectives on Conservation, Tourism, and Repatriation of Artefacts at the National Museum, Benin City, Nigeria - Mba, Okechukwu Joshua (Advances in Social Sciences Research Journal, 2025)
Museums serve as vital institutions for preserving a society’s cultural heritage and identity, preventing its erosion or extinction, a pressing concern for most African nations. The study examines the National Museum Benin City’s role in this endeavor, assessing its curatorial and public perspectives on conservation, tourism, and artifact repatriation. Drawing on historical sources, ethnographic fieldwork including researcher observation at the museum, interviews with museum curators, the locals and museum visitors. The study adopts a mixed method approach of data collection employing both semi-structured interviews and questionnaire surveys. Collected data were evaluated using NVivo 15 analytical software and through descriptive statistics. The findings revealed that despite the museum’s contributions to cultural tourism, education, and repatriation advocacy, it faces persistent challenges including funding gaps, infrastructural limitations, inadequately trained personnel and slow repatriation efforts. The study concludes that the National Museum Benin City’s can establish a replicable model for heritage preservation by formalizing community-museum partnerships, sustainable funding, investing in comprehensive staff training, as well as improving its efforts for repatriation of cultural artefacts and greater collaboration between the museum and tour agencies for its tourism development.